Prevalência de Staphylococcus aureus resistentes à meticilina (MRSA) em granjas de suínos - Santos, Silvana Cristina Lima dos (2015)
Aimed to investigate the prevalence, the pattern of antimicrobial susceptibility and the genotypic ratio of Staphylococcus aureus (S. aureus) isolated from pigs in differents age groups. Based of calculation of sample size, were collected 282 nasal swabs of pigs from three differents farms in Northest, located in the citys of Areia and Santa Rita (Paraiba State) and Itapetim (Pernambuco State). Considering the emerging public health significance of methicillin-resistant Staphylococcus aureus (MRSA), parallel protocol was performed to isolate these microorganism in all samples. After conventional microbiological isolation and conducting tests for phenotypic and genotypic identification of Staphilococcus genus, PCR was conducted to identify molecular markers specific of S. aureus. Among the samples analyzed, 48.9% (138/282) were positive for Staphylococcus spp., among with 15.94% (22/138) were positive for S. aureus. The prevalence of S. aureus in the Farm 1 was 2.07% (CI = 0.71, 5.91) and Farm 3 was 2.97% (CI = 1.91, 4.59). It was not isolated S. aureus from the animals of Farm 2. Among the markers for the S. aureus species, femA gene was the most frequently found. Resistance to at least one antimicrobial agent was detected in all investigated S. aureus, with the higthest rates observed to clindamycin (100%), ampicillin (100%) and penicillin (100%), followed by chloraphenicol (95.45%) and azithromycin (90.91). Of all S. aureus, 63.64% (14/22) were resistant to cefoxitin, confirming be resistant to methicillin (MRSA). The genetic similarity analysis by Rep-PCR indicated the grouping of bacteria due to its origin. Also, isolates from different sectors of production have become indistinguishable, indicating that S. aureus strains can infect pigs at different age groups.